Scoring system for the prediction of severe acute pancreatitis in children. Issue 1 (25th November 2014) - Suzuki, Mitsuyoshi; Saito, Nobutomo; Naritaka, Nakayuki; Nakano, Satoshi; Minowa, Kei; Honda, Yuka; Ohtsuka, Yoshikazu; Yamataka, Atsuyuki; Shimizu, Toshiaki
Abstract: Background: The lack of an accurate scoring system for pediatric acute pancreatitis could cause delays in appropriate clinical management and increase the risk of progressive life‐threatening complications. We investigated a modified Ministry of Health, Labour and Welfare of Japan (JPN) scoring system that uses pediatric systemic inflammatory response syndrome (SIRS) score, age, and weight to establish a more useful scoring system for children. Methods: A retrospective chart review was conducted of pediatric patients with acute pancreatitis who were admitted to Juntendo University Hospital between 1985 and 2011. The sensitivity, specificity, and positive and negative predictive values of the pediatric JPN scoring system were calculated and then compared with those of previously developed scoring systems. Results: The patient group consisted of 145 patients (88 girls, 57 boys). The pediatric JPN score had greater sensitivity (80%) than the Ranson (60%), modified Glasgow (50%), and DeBanto (60%) scores. The specificity was 96% for the pediatric JPN score, 94% for the Ranson score, 99% for the modified Glasgow score, and 86% for the DeBanto score. Conclusion: The pediatric JPN score can be used to predict severe acute pancreatitis during the initial medical assessment.